Reinforced Concrete Columns Insulated by Different Gypsum Layers Exposed to 900°C One Side Fire Flame - Al-Jadiri, Mohanad Salih Farhan; Said, Abdul Muttalib I. (Engineering, Technology & Applied Science Research, 2023)
This study investigated the effect of high-temperature fire flame on reinforced concrete columns coated with a layer of gypsum insulation. Six samples were cast and cured in a hot water bath at 67°C, covered on one side by 10 and 20 mm thick layers of gypsum plaster. The samples were exposed to a 900°C fire flame in a hydrocarbon fire furnace for one and two hours. The results showed that the gypsum plaster layer prevented a high-temperature rise within the core of the column. The differences between all gypsum-coated columns varied compared to those of the reference samples. The gypsum-coated columns had reduced axial displacements and no spalling and visible cracks on their faces. The improvement in the compressive strength of concrete will be discussed in a future paper. This study was carried out following ACI-318 and ASTM C1529.